PoZitively Transformative: The Transformative Learning of People Living with HIV - Lisa M. Baumgartner; Keegan N. David (Adult Education Research Conference, 2009)
The purpose of this study was to investigate meaning making in People Living with HIV (PLWH) as a chronic illness. Findings confirm those of Courtenay, Merriam and Reeves (1998) who examined meaning making in PLWHAs when HIV/AIDS was a terminal illness. Contextual factors that mediate meaning making were uncovered.